2005
DOI: 10.1002/pts.699
|View full text |Cite
|
Sign up to set email alerts
|

‘Inclusive’ design for containers: improving openability

Abstract: For many years the standard engineering design approach has been to design for the most common size or ability and hence ensuring that your product is applicable to the broadest proportion of society. Recently, however, this approach has been seen to be flawed, particularly with regards to consumer packaging (although there many examples in other industries, such as transport). This paper outlines a new approach to packaging design that has been termed 'inclusive' design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 1 publication
1
35
0
1
Order By: Relevance
“…According to the results, in most cases, men show slightly higher peel forces than women. This is in accordance with other research [29][30] which mentioned that human strength capability of opening packages depends on age. Rowson and Yoxall [30] also reported that typically, women chose a grip that maximized their opportunity of opening the closure and that this grip choice was more limited than that available for men.…”
Section: Fig 6-peel Force and Elongation At Break Of Machine And Humsupporting
confidence: 93%
“…According to the results, in most cases, men show slightly higher peel forces than women. This is in accordance with other research [29][30] which mentioned that human strength capability of opening packages depends on age. Rowson and Yoxall [30] also reported that typically, women chose a grip that maximized their opportunity of opening the closure and that this grip choice was more limited than that available for men.…”
Section: Fig 6-peel Force and Elongation At Break Of Machine And Humsupporting
confidence: 93%
“…Many previous studies of human strength have been performed by various groups. However, as noted in work on determining design limits for consumer packaging, 4 these studies did not properly replicate the opening process and, therefore, the results cannot be used for packaging design with great certainty.…”
Section: Research Drivers and Aimsmentioning
confidence: 84%
“…3 Langley et al defined 'Openability' as easy for consumers to access a product and considered it a crucial factor for packaging industry. 4,5 In another study, Yoxall et al used the uncertainty analysis to show the influence of parameters on opening torque. 6 Hence the 'peak' removal torque of a cap and bottle assembly is critical because it indicates both sealing performance and ease of opening.…”
Section: Introductionmentioning
confidence: 98%